MAIN TECHNOLOGICAL FACTORS AFFECTING THE PROPERTIES OF LOW-DOPED LAYERS AND TRANSISTOR n+-p0 – n0 STRUCTURES - A. M. Sultanov; J. Z. Mirzarayimov (European Science Publishing, 2024)
In this work, a study was made of the features of obtaining high-voltage gallium arsenide p0–n0 - junctions by liquid epitaxy The regimes of epitaxial growth are determined, which ensure the production of high-voltage p-n junctions based on lightly doped GaAs for the creation of submenu and picosecond semiconductor switches. The influence of technological factors on the electro physical properties of epitaxial layers has been studied. It has been established that with an increase in the temperature of the onset of crystallization and the size of the growth gap, the thicknesses of the low-resistance part of the p0-region and the breakdown voltages n+-p0–n0 of the structures increase, while the values of the transmission coefficient decrease. The influence of the main technological factors on the static and dynamic characteristics of the created devices has been studied. It has been established that a change in the thickness of the solution-melt from 1 mm to 3 mm, or the temperature of the onset of crystallization from 850 ⁰С to 950 ⁰С, leads to a decrease in the value of the transmission coefficient n+-p0–n0 of structures, an increase in the turn-on voltage, control current, and an increase in the voltage value the beginning of an abnormally rapid increase from 50 V to 400 V. There is a simultaneous increase in the duration of the current rise, a decrease in the stability of the switching moment, and an increase in the values of the residual voltage.